167k views
5 votes
How do u simplify y^4z^3/y^6z^2

2 Answers

3 votes

Answer:

z^5/y^2

Explanation:

Simplify: z^3/y^6

Equation at the end of step 1 :

((y4) • z^3/y^6 ) • z^2

Multiplying exponential expressions :

z^3 multiplied by z^2 = z^(3 + 2) = z^5

And you will have your answer

User Agent Zebra
by
7.2k points
3 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] ~\dotfill\\\\ \cfrac{y^4z^3}{y^6z^2}\implies \cfrac{z^3z^(-2)}{y^6 y^(-4)}\implies \cfrac{z^(3-2)}{y^(6-4)}\implies \cfrac{z}{y^2}

User Colin Coghill
by
5.7k points